Religiosity and Happiness Among the Abdi Dalem of Yogyakarta Palace: A Quantitative Study - Ar' Ridho, Muhammad; Akhrani, Lusy Asa (Mediapsi, 2025)
Happiness is often associated with wealth, but abdi dalem with their low incomes maintain high levels of happiness. Cultural influences give abdi dalem a unique perspective on happiness. This study examines the role of religiosity in the happiness of the Abdi Dalem of Yogyakarta Palace using quantitative methods. Data were collected through a questionnaire measuring religiosity and happiness, distributed directly to respondents. The sample consisted of 147 Abdi Dalem of Yogyakarta Palace with predefined criteria. The mean age of the respondents was 64.79 with a standard deviation of 12.12. The Oxford Happiness Questionnaire-Short Form (OHQ-SF) was used to measure the happiness variable, and the Centrality of Religiosity Scale (CRS-10) to measure the religiosity variable. Through simple linear regression analysis, it was found that religiosity has a positive effect on happiness, with a contribution rate of 4%. These findings suggest that religiosity, as an internalized and culturally embedded construct, plays a foundational yet limited statistical role in the happiness of the Abdi Dalem. The results offer valuable insights into culturally rooted well-being and highlight the importance of religious commitment in traditional communities